Effect of an educational intervention based on the theory of planned behavior on improving medication adherence in patients with multiple sclerosis treated with injectable disease-modifying drugs: randomized controlled trial - Sara Hamtaeigashti; Mohsen Shamsi; Mohammad Ali Sahraian; Raheleh Soltani; Amir Almasi-Hashiani (BMC, 2023)
Abstract Background Adherence to prescribed treatment in chronic diseases, as occurs in multiple sclerosis (MS), is a critical factor for a successful therapeutic response. This study aimed to investigate the effect of educational program based on Theory of Planned Behavior (TPB) on treatment adherence in patients with multiple sclerosis (MS) receiving injectable immunomodulatory drugs. Methods The present study is an educational randomized controlled trial research that was conducted on 100 patients with MS who had gone to MS clinic in Tehran city (Iran). The samples were randomly assigned to the intervention (N = 50) and control groups (N = 50). Data collection instrument was a researcher-made questionnaire based on TPB. Then, educational program was performed for the intervention group through four educational sessions. After three months, data collection was repeated for the two groups and data were analyzed. Results The knowledge and performance of the intervention group on treatment adherence drugs increased from 56.25 ± 20.3 to 78.31 ± 15.57 and 56.22 ± 5.76 to 71.62 ± 12.01 after the education respectively (p < 0.001). The mean of construct of TPB in the intervention group also increased after the intervention (p < 0.05). Conclusion Applying the TPB model proved is very effective in developing an educational program for patients with MS, to enhance treatment adherence drugs. Besides such programs, follow-up education for controlling and monitoring are highly recommended. Trial registration This trial has been registered at Iranian Registry of Clinical Trials, IRCT20210808052109N1. Prospectively registered at 12-Aug-2021, (12/8/2021) available at: URL: https://en.irct.ir/trial/57994